2021
DOI: 10.1590/1983-1447.2021.20190283
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nursing diagnosis educational software program

Abstract: Introduction The human-computer interaction is essential in simulated electronic systems associated with teaching-learning activities. Interactive clinical cases reinforce the diagnostic reasoning ability, a stage of the advanced Nursing Process. Purpose To build educational software, based on NANDA International, to improve the accuracy of nursing diagnoses. Method Methodological study in three stages: preparation and validation of case studies; construction; homologation and evaluation. Held between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Aligned with this issue, CuidarTech ® Cirúrgico brings 10 case studies integrated with the standardized language systems of nursing for training nurses 17,20 . A study in which educational software was developed using case studies showed an improvement in the accuracy of nursing diagnoses, helping in the teachinglearning process and allowing more appropriate interventions, providing greater patient safety 21 .…”
Section: /12mentioning
confidence: 99%
See 1 more Smart Citation
“…Aligned with this issue, CuidarTech ® Cirúrgico brings 10 case studies integrated with the standardized language systems of nursing for training nurses 17,20 . A study in which educational software was developed using case studies showed an improvement in the accuracy of nursing diagnoses, helping in the teachinglearning process and allowing more appropriate interventions, providing greater patient safety 21 .…”
Section: /12mentioning
confidence: 99%
“…By establishing priorities, they support the development of cognition, communication, procedures and teamwork skills. In the Nursing Process, using case studies by nurses facilitates the understanding of nursing diagnoses and interventions, contributing to improving cognitive abilities, because cases provide examples of diagnostic reasoning principles 13,21 .…”
Section: /12mentioning
confidence: 99%
“…In this context, we highlight the growth in the production of educational technologies in health that contribute to the improvement of care and enhance the construction of knowledge and empowerment of users. Presently, mobile apps represent a relevant instrument in the collaboration of innovative and informative educational learning ( 9 , 10 , 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative that, once we have identified human responses in adolescents with cancer, we proceed to identify nursing diagnoses associated with them. A precise understanding of human responses and the subsequent formulation of nursing diagnoses for both individuals and their families can lead to more appropriate intervention choices and positive outcomes 17…”
Section: Introductionmentioning
confidence: 99%
“…A precise understanding of human responses and the subsequent formulation of nursing diagnoses for both individuals and their families can lead to more appropriate intervention choices and positive outcomes. 17 The exploration of human responses in adolescents with oncological diseases is a crucial area of investigation, presenting a unique challenge for healthcare professionals due to the inherent complexities of this stage of human development. 4 5 Professionals, particularly nurses, should be well-informed and discerning regarding the transformations in the lives of adolescents following a cancer diagnosis, as they play a pivotal role in nursing care, addressing the multifaceted changes affecting the entirety of the individual.…”
Section: Introductionmentioning
confidence: 99%